Inter-assay diagnostic accuracy of cerebrospinal fluid kappa free light chains for the diagnosis of multiple sclerosis - Dekeyser, Cathérine; De Kesel, Pieter; Cambron, Melissa; Vanopdenbosch, Ludo; Van Hijfte, Liesbeth; Vercammen, Martine; Laureys, Guy (Frontiers in Immunology, 2024)
Background Cerebrospinal fluid (CSF) kappa free light chain (κFLC) measures gained increasing interest as diagnostic markers in multiple sclerosis (MS). However, the lack of studies comparing assay-dependent diagnostic cutoff values hinders their use in clinical practice. Additionally, the optimal κFLC parameter for identifying MS remains a subject of ongoing debate. Objectives The aim of this study was to compare same-sample diagnostic accuracies of the κFLC index, κIgG index, CSF κFLC/IgG ratio, and isolated CSF κFLC (iCSF-κFLC) between two reference centers using different methods. Methods Paired serum and CSF samples were analyzed for κFLC and albumin concentrations by Freelite®-Optilite (Sint-Jan Bruges hospital) and N Latex®-BNII (Ghent University hospital). Diagnostic performance to differentiate MS from controls was assessed using ROC curve analysis. Results A total of 263 participants were included (MS, n = 80). Optimal diagnostic cutoff values for the κFLC index (Freelite®-Optilite: 7.7; N Latex®-BNII: 4.71), κIgG index (Freelite®-Optilite: 14.15, N Latex®-BNII: 12.19), and CSF κFLC/IgG ratio (Freelite®-Optilite: 2.27; N Latex®-BNII: 1.44) differed between the two methods. Sensitivities related to optimal cutoff values were 89.9% (Freelite®-Optilite) versus 94.6% (N Latex®-BNII) for the κFLC index, 91% (Freelite®-Optilite) versus 92.2% (N Latex®-BNII) for the κIgG index, and 81.3% (Freelite®-Optilite) versus 91.4% (N Latex®-BNII) for the CSF κFLC/IgG ratio. However, for iCSF-κFLC, optimal diagnostic cutoff values (0.36 mg/L) and related specificities (81.8%) were identical with a related diagnostic sensitivity of 89.9% for Freelite®-Optilite and 90.5% for N Latex®-BNII. The diagnostic performance of the κFLC index [area under the curve (AUC) Freelite®-Optilite: 0.924; N Latex®-BNII: 0.962] and κIgG index (AUC Freelite®-Optilite: 0.929; N Latex®-BNII: 0.961) was superior compared to CSF oligoclonal bands (AUC: 0.898, sensitivity: 83.8%, specificity: 95.9%). Conclusions The κFLC index and the κIgG index seem to be excellent markers for identifying MS, irrespective of the method used for κFLC quantification. Based on the AUC, they appear to be the measures of choice. For all measures, optimal cutoff values differed between methods except for iCSF-κFLC. iCSF-κFLC might therefore serve as a method-independent, more cost-efficient, initial screening measure for MS. These findings are particularly relevant for clinical practice given the potential future implementation of intrathecal κFLC synthesis in MS diagnostic criteria and for future multicentre studies pooling data on κFLC measures.